Wound management - Earthbound Media; Concept Media, Inc. (Irvine, Calif. : Earthbound Media ; distributed by Concept Media, 2006)
The purpose for the learner is to have basic understanding of the nursing care involved in treating wounds.
pt. 1. Wound healing -- pt. 2. Wound evaluation -- pt. 3. Arterial wounds -- pt. 4. Venous wounds -- pt. 5. Neuropathic wounds -- pt. 6. Pressure ulcers -- pt. 7. Atypical wounds -- pt. 8. Debridement -- pt. 9. Dressings -- pt. 10. Physical modalities -- pt. 11. Clinical application questions -- pt. 12. Instructor's guides -- pt. 13. Self-grading tests
System requirements: IBM PC-compatible, Pentium 133 or faster processor with 64 MB; Microsoft Windows 98 or higher; 4X or faster CD-ROM drive; 640 x 480 video card capable of displaying thousands of colors; 13" monitor capable of thousands of colors
Narrator
Compact disc
Closed-captioned
No Masters
Keywords: Wounds and injuries -- Nursing; Wounds and injuries -- Treatment; Bandages and bandaging